Influence of ecoregional and lifestyle factors on growth and body composition of Indian children and adolescents aged 9–18 years—A multicenter study. Issue 4 (21st December 2022) - Vispute, Smruti; Mandlik, Rubina; Khadilkar, Anuradha; Gondhalekar, Ketan; Patwardhan, Vivek; Khadilkar, Vaman
Abstract: Objectives: Ecoregion comprises all the environmental factors such as climate, vegetation, geomorphology, and soil taken together. The objectives of this study were to (1) assess differences in growth and body composition (BC) in 9–18‐year‐old children and adolescents (CA), across six ecoregions of India, (2) evaluate and compare the magnitude of the effect of ecoregional and lifestyle factors (LSF) on growth and BC in urban ( U ) and rural ( R ) children and adolescents, and (3) reassess the applicability of Bergmann's Rule and Allen's Rule to humans. Subjects and Methods: Data on 1845 CA (925 boys; 920 girls) were collected (2016–2017) from urban and rural areas of six ecoregions of India. Anthropometric and BC parameters were measured; Z‐scores were computed. Lifestyle Index score (LIS) based on LSF—(socioeconomic status [SES], diet, physical activity) was computed (categorized as low, medium, high—indicates better LSF). Univariate analysis was performed to estimate effect size. Results: Significant differences were observed in growth and BC across urban and rural ecoregions. CA with high LIS were taller and heavier than those with low LIS ( p  < .05). Ecoregion had greater effect on growth (Partial eta square ( η 2 ) for R  = 0.136 vs. U  = 0.057) and BC ( η 2 for R  = 0.094 vs. U  = 0.058) of rural CA than urban ( p  < .01). LSF had more effect on the BC of urban CA ( η 2  = 0.017) than rural ( η 2  = 0.002, p  < .01). Conclusion: Disparities among the six ecoregions were not large enough to fully support Bergmann's Rule and Allen's Rule. Ecoregion had greater effect on growth and BC of rural CA than urban, while lifestyle factors had more effect on the BC of urban CA.